1998
DOI: 10.1016/s0014-5793(98)01284-8
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of agonist and antagonist interactions in serotonin 1A receptors by alcohols

Abstract: The serotonin type 1A (5-HT Ie ) receptors are members of a superfamily of seven transmembrane domain receptors that couple to GTP binding regulatory proteins (Gproteins). Serotonergic signalling has been shown to play an important role in alcohol tolerance and dependence. We have studied the effects of alcohols on ligand (agonist and antagonist) binding to bovine hippocampal 5-HT Ie receptor in native as well as solubilized membranes. Our results show that alcohols inhibit the specific binding of the agonist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…The direct effect of various alcohols on ligand binding and G-protein coupling of the bovine hippocampal 5-HT 1A receptor has been examined by Chattopadhyay (1998b, 2000). The results show that alcohols inhibit the specific binding of the agonist 8-OH-DPAT (except in case of ethanol) and the antagonist p-MPPF to 5-HT 1A receptors in a concentration dependent manner (Harikumar and Chattopadhyay, 1998b). These results further show that the action of alcohols on the hippocampal 5-HT 1A receptor could be modulated by guanine nucleotides .…”
Section: Membrane Biology Of Serotonin 1a Receptors: Receptor-cholestmentioning
confidence: 56%
“…The direct effect of various alcohols on ligand binding and G-protein coupling of the bovine hippocampal 5-HT 1A receptor has been examined by Chattopadhyay (1998b, 2000). The results show that alcohols inhibit the specific binding of the agonist 8-OH-DPAT (except in case of ethanol) and the antagonist p-MPPF to 5-HT 1A receptors in a concentration dependent manner (Harikumar and Chattopadhyay, 1998b). These results further show that the action of alcohols on the hippocampal 5-HT 1A receptor could be modulated by guanine nucleotides .…”
Section: Membrane Biology Of Serotonin 1a Receptors: Receptor-cholestmentioning
confidence: 56%
“…It is therefore important to determine the actual concentration of the anesthetics partitioned into the membrane while considering their effects on the ligand-binding properties of the 5-HT 1A receptor. The concentrations of the local anesthetics in membranes can be determined from their membrane/buffer partition coefficients (De Paula and Schreier, 1995) using a formalism previously developed by us (Harikumar and Chattopadhyay, 1998b) to determine partitioning of alcohols into membranes. Calculations by this approach using literature values of the membrane/buffer partition coefficients of tertiary amine local anesthetics (De Paula and Schreier, 1995) showed that most (>99%) of the added anesthetics got partitioned into the membrane due to their high partition coefficient values in the range of concentrations used by us.…”
Section: Discussionmentioning
confidence: 99%
“…The final concentration of ethanol in the assay tubes was maintained at 0.05% (v/v). Control experiments showed that ethanol at this concentration did not affect the ligand-binding properties of the receptor (Harikumar and Chattopadhyay, 1998b). The incubation was terminated by rapid filtration under vacuum in a Millipore multiport filtration apparatus through Whatman GF/B (1.0 µm pore size) 2.5 cm diameter glass microfiber filters which were presoaked in 0.15% polyethylenimine for 3 h (Bruns et al, 1983).…”
Section: Receptor Binding Assays Of Hippocampal Membranes Treated Witmentioning
confidence: 99%
“…In addition, the 5-HT 1A receptor antagonists represent a major class of molecules with potential therapeutic effects in anxiety-or stress-related disorders [30]. We have earlier solubilized and partially purified the 5-HT 1A receptor from bovine hippocampus [31,32] and have shown modulation of ligand binding to the bovine hippocampal 5-HT 1A receptor by metal ions, guanine nucleotides, alcohols, local anesthetics, membrane cholesterol, and covalent modifications of the disulfides and sulfhydryl groups [33][34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%